Elevation of post mortem vitreous humour sodium and chloride levels can be used as a reliable test in cases of suspected salt water drowning when the immersion times are less than one hour. (September 2016) - Garland, J.; Tse, R.; Oldmeadow, C.; Attia, J.; Anne, S.; Cala, A.D.
Graphical abstract: Highlights: ⿢ PMVSC is a useful test for suspected salt water drowning. ⿢ When immersion time is less than one hour, salt water drowning elevates PMVSC. ⿢ When immersion time is more than one hour, PMVSC can increase due to immersion. Abstract: Background: Previous studies in salt water drowning deaths (SWD) demonstrated an observable elevation of post mortem vitreous sodium and chloride (PMVSC) levels. It remains unclear what the underlying mechanism responsible for this change is: whether this is due to rapid electrolyte changes from salt water inhalation/ingestion during drowning or from electrolyte diffusion and/or osmosis across the outer coats of the eyeballs during immersion. A recent animal study using sacrificed bovine eyeballs immersed in salt water demonstrated no significant elevations in PMVSC when immersed for less than one hour. Assuming similar physical properties between human and bovine, we extrapolate that an elevation in PMVSC in SWD with immersion times of less than one hour (SWD-1) would not be from immersion, but from drowning. Aim: Investigate whether there is an elevation in PMVSC in SWD-1. Methods: Retrospective study comparing PMVSC in SWD-1 with controls from 2012 to 2015 inclusive. Results: PMVSC in SWD-1 was significantly elevated compared with controls. A PMVSC of 259 mmol/L has a sensitivity, specificity and likelihood ratio of 0.9, 0.9 and 7.6, respectively. Conclusion: The elevation in PMVSC in SWD-1 is due to drowning. A PMVSC of 259 mmol/L and above is a reliable ancillary test in diagnosing drowning in bodies immersed in salt water for less than one hour.